2023
DOI: 10.1017/s0029665123002689
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent nutrition and health: characteristics, risk factors and opportunities of an overlooked life stage

Abstract: Adolescence is a pivotal, yet frequently overlooked, period of life, with this age group often no longer receiving the focus, care and protection devoted to other life stages. Nutritional vulnerability increases in adolescence due to heightened nutritional requirements, yet the quality of the diets consumed by this age group often deteriorates significantly. Poor-quality dietary patterns and insufficient nutrient intakes are frequently observed amongst adolescents both in Ireland and globally. This deteriorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 180 publications
0
3
0
Order By: Relevance
“…In fact, the intake was almost twice less than the recommended amount, which is in accordance with the HELENA study conducted on adolescents in Europe, where it was confirmed that adolescents ate only half of the recommended amount of fruits and vegetables [ 12 ]. Inadequate fruit consumption seems to be reported among adolescents on a global level [ 32 ]. Specifically, inadequate fruit consumption among Croatian adolescents could be partly explained by relatively high cost per 1000 kcal from fruit, in comparison with other food groups, as shown in a report for the Croatian market [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the intake was almost twice less than the recommended amount, which is in accordance with the HELENA study conducted on adolescents in Europe, where it was confirmed that adolescents ate only half of the recommended amount of fruits and vegetables [ 12 ]. Inadequate fruit consumption seems to be reported among adolescents on a global level [ 32 ]. Specifically, inadequate fruit consumption among Croatian adolescents could be partly explained by relatively high cost per 1000 kcal from fruit, in comparison with other food groups, as shown in a report for the Croatian market [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequacies in diet and physical activity, and their health consequences, occur with varying intensity depending on age, gender, nutritional knowledge of both adolescents and their parents, susceptibility to dietary trends, family characteristics, parenting style and parents’ lifestyle, parents’ work, and the level of social and living conditions, as well as environmental factors such as school food policy [ 9 , 14 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…School is the second environment, coming next after family, that influences a proper lifestyle, including the nutrition of children and adolescents. The school’s activities cover formal nutritional education during lessons in accordance with the core curriculum, the meals and foods available at the school (in the canteen, school shop, vending machine), additional activities related to the promotion of a healthy lifestyle, e.g., external and internal educational programs, events organized at the school, e.g., child’s day, days thematically related to nutrition, as well as the frequency of physical education classes and additional physical activities [ 29 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%